BUILDING ATTITUDES AND MOTIVATION IN UNDERGRADUATES: THE ROLE OF LEARNING MANAGEMENT SYSTEM (LMS) IN CROSS RIVER STATE, NIGERIA (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
Learning Management Systems (LMS) have emerged as transformative tools in higher education, fostering student engagement and motivation through interactive and accessible learning environments. This study investigates the role of LMS in shaping undergraduates’ attitudes and motivation in Cross River State, Nigeria, a region navigating educational modernization amidst infrastructural challenges. Employing a mixed-methods approach, primary data were collected via surveys and focus group discussions with 200 undergraduates and 40 faculty members across three institutions: University of Calabar, Cross River University of Technology, and Arthur Jarvis University. Findings indicate that LMS platforms, such as Moodle and Google Classroom, significantly enhance student motivation, self-directed learning, and positive attitudes toward education, with 78% of students reporting improved engagement. However, barriers like unreliable internet and limited digital literacy impede optimal use. Demographic analysis reveals a participant pool of 55% male and 45% female students, aged 18–25, with faculty showing varied LMS proficiency. The study highlights the need for robust infrastructure, tailored training, and inclusive LMS design to maximize impact. Recommendations include policy-driven investments in digital connectivity and faculty development programs to sustain LMS adoption. This research underscores LMS as a catalyst for educational transformation in Cross River State, offering a scalable model for enhancing undergraduate learning experiences in Nigeria.